Resolva, aplicando a fórmula de Bhaskara:
a) x² + 5x + 6 = 0
b) -x² + 5x - 6 = 0
c) x² + 7x + 10 = 0
d) -x² - 7x - 10 = 0
e) x² + 5x + 4 = 0
f) 2x² - x + 3 = 0
g) 3x² + 4x + 1 = 0
h) 5x² + 4x - 1 = 0
i) 2x² + x - 3 = 0
j) x² + 7x + 12 = 0
k) x² + 6x + 9 = 0
l) x² + x - 1 = 0
m) x² - 2x + 1 = 0

1

Respostas

A melhor resposta!
2014-05-01T18:15:09-03:00
A) x² + 5x + 6 = 0
Δ = 5² - 4 . 1 . 6                           X = - 5 +- √1  / 2 . 1
Δ = 25 - 24                                  X = - 5 +- 1 / 2
Δ = 1
x' = - 5 + 1 / 2 => - 4 / 2 = - 2               x" = - 5 - 1 / 2 => - 6 / 2 = - 3
        S = {- 2, - 3}

b) - x² + 5x - 6 = 0
Δ = 5² - 4 . (- 1) . (- 6)                             X = - 5 +- √1  / 2 . (- 1)
Δ = 25 - 24                                            X = - 5 + - 1  / - 2
Δ = 1
x' = - 5 + 1 / - 2 => - 4 / - 2 = 2                x" = - 5 - 1 / - 2 => - 6 / - 2 = 3
         S = {2,3}

c) x² + 7x + 10 = 0
Δ = 7² - 4 . 1 . 10                               X = - 7 +- √9 / 2 . 1
Δ = 49 - 40                                        X = - 7 +- 3  / 2
Δ = 9
x' = - 7 + 3 / 2 => - 4 / 2 = - 2              x" = - 7 - 3 / 2 => - 10 / 2 = - 5
        S = {- 2, - 5}

d) - x² - 7x - 10 = 0
Δ = (- 7)² - 4 . (- 1) . (- 10)                      X = - (- 7) +- √9  / 2 . (- 1)
Δ = 49 - 40                                           X = 7 +- 3  / - 2
Δ = 9
x' = 7 + 3 / - 2 => 10 / - 2 = - 5                x" = 7 - 3 / - 2 => 4 / - 2 = - 2
          S = {- 5, - 2}

e) x² + 5x + 4 = 0
Δ = 5² - 4 . 1 . 4                               X = - 5 +- √9  / 2 . 1
Δ = 25 - 16                                      X = - 5 +- 3  / 2
Δ = 9
x' =  - 5 + 3 / 2 = - 2 / 2 = - 1                x" = - 5 - 3 / 2 => - 8 / 2 = - 4
         S = {- 1, - 4}

f) 2x² - x + 3 = 0
Δ = (- 1)² - 4 . 2 . 3                           
Δ = 1 - 24                                      Não há raízes.
Δ = - 23

g) 3x² + 4x + 1 = 0
Δ = 4² - 4 . 3 . 1                          X = - 4 +- √4  / 2 . 3
Δ = 16 - 12                                 X = - 4 +- 2  / 6
Δ = 4
x' = - 4 + 2 / 6 => - 2 / 6 (÷2) = - 1/3 ou 0,33          x" = - 4 - 2 / 6 = - 6 / 6 = - 1
            S = {- 1/3, - 1}    ou    S = {0,33, - 1)

h) 5x² + 4x - 1 = 0
Δ = 4² - 4 . 5 . (- 1)                       X = - 4 +- √36  / 2 . 5
Δ = 16 + 20                                 X = - 4 +- 6  / 10
Δ = 36
x' = - 4 + 6 / 10 => 2 / 10 (÷2) => 1/5 ou 0,2         x" = - 4 - 6 / 10 => - 10 / 10 = - 1
         S = {1/5, - 1}   ou   S = {0,2, - 1}

i) 2x² + x - 3 = 0
Δ = 1² - 4 . 2 . (- 3)                          X = - 1 +- √25  / 2 . 2
Δ = 1 + 24                                      X = - 1 +- 5  / 4
Δ = 25
x' = - 1 + 5 / 4 => 4 / 4 = 1                   x" = - 1 - 5 / 4 => - 6 / 4 (÷2) => - 3/2 ou - 1,5
          S = {1, - 3/2}    ou   S = {1, - 1,5}

j) x² + 7x + 12 = 0
Δ = 7² - 4 . 1 . 12                         X = - 7 +- √1  / 2 . 1
Δ = 49 - 48                                  X = - 7 +- 1  / 2
Δ = 1
x' = - 7 + 1 / 2 => - 6 / 2 = - 3                 x" = - 7 - 1 / 2 => - 8 / 2 = - 4
          S = {- 3, - 4}

k) x² + 6x + 9 = 0
Δ = 6² - 4 . 1 . 9                           X = - 6 +- √0  / 2 . 1
Δ = 36 - 36                                  X = - 6 / 2
Δ = 0                                          X = - 3
Há apenas 1 raíz.
           S = {- 3}

l) x² + x - 1 = 0
Δ = 1² - 4 . 1 . (- 1)                     X = - 1 +- √5  / 2 . 1
Δ = 1 + 4                                   X = - 1 +- 2,24 / 2
Δ = 5                                  
x' = - 1 + 2,24 / 2 => 1,24 / 2 = 0,62            x" = - 1 - 2,24 / 2 => - 3,24 / 2 = - 1,62
          S = {0,62, - 1,62}

m) x² - 2x + 1 = 0
Δ = (- 2)² - 4 . 1 . 1                   X = - (- 2) +- √0  / 2 . 1
Δ = 4 - 4                                 X =  2 / 2 
Δ = 0                                      X = 1
Há apenas 1 raíz.
          S = {1}
2 5 2